Capecitabine in adjuvant radiochemotherapy for gastric adenocarcinoma - But Hadžić, Jasna (Radiology and oncology (Ljubljana), 2014)
Background. In patients with non-metastatic gastric cancer surgery still remains the treatment of choice. Postoperative radiochemotherapy with 5-fluorouracil and leucovorin significantly improves the treatment outcome. The oral fluoropyrimidines, such as capecitabine, mimic continuous 5-fluorouracil infusion, are at least as effective as 5-fluorouracil, and such treatment is more comfortable for the patients. Patients and methods. In the period from October 2006 to December 2009, 101 patients with gastric cancer in stages Ib-IIIc were treated with postoperative chemoradiation with capecitabine. Distal subtotal resection of the stomach was performed in 46.3%, total resection in 50.5% and multivisceral resection in 3.2% of patients. The main endpoints of this study were loco-regional control (LRC), disease-free survival (DFS), disease-specific survival (DSS) and overall survival (OS). The rates of acute side-effects were also estimated. Results. Seventy-seven percent of patients completed the treatment according to the protocol. The median followup time of all patients was 3.9 years (range: 0.4-6.3 years) and in survivors it was 4.7 years (range: 3.2-6.3 years). No death occurred due to the therapy. Acute toxicity, such as nausea and vomiting, stomatitis, diarrhoea, hand-foot syndrome and infections of grade 3 or 4, occurred in 5%, 1%, 2%, 8.9% and 18.8% of patients, respectively. On the close-out date 63.4% patients were still alive and with no signs of the disease. The 4-years follow-up survey showed that LRC, DFS, DSS and OS were 95.5%, 69.2%, 70.7%, and 66.2%, respectively. Higher pN-stage and splenectomy were found to be independent prognostic factors for all four types of survival and perineural invasion and lower treatment intensity for DFS, DSS and OS.
Keywords: adjuvant therapy; adjuvantno zdravljenje; gastric cancer; radiochemotherapy; radiokemoterapija; rak (medicina); želodec